Optimization of Formulation and Physical Evaluation of Peel-Off Gel Face Mask from Clove Leaf Essential Oil (Syzygium aromaticum L.) - Miftahul Jannah, Nadia; Prasetyo, Yogi (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Acne is an inflammatory infection triggered by Propionibacterium acnes bacteria. Clove leaf essential oil (Syzygium aromaticum L.) has attracted attention as a potential active ingredient in skincare products, such as peel-off gel face masks, due to its anti-inflammatory properties. This study aims to develop a natural, effective, and safe skincare product for treating acne using clove leaf essential oil as the active ingredient. The active ingredient was 2% essential oil, with formulation optimization of PVA (1–2.5%) and propylene glycol (5–6.5%). The physical evaluation of the formulations included organoleptic properties, homogeneity, pH, spreadability, viscosity, and drying time. The optimum formulation of the peel-off gel face mask containing clove leaf essential oil was achieved with a PVA concentration of 1.163% and propylene glycol at 6.333%, with a desirability value of 1.000. The physical evaluation results of the optimum formula showed a pH value of 5.90, a spreadability of 6.60 cm, a drying time of 26.08 minutes, and a viscosity of 30,682.50 cps.